ANALISIS KINERJA KEUANGAN PEMERINTAH KOTA JAMBI TAHUN 2010 – 2019 - Emilia Fornia; Mukhzarudfa Mukhzarudfa; Muhammad Gowon (Jurnal Akuntansi & Keuangan Unja, 2021)
The application of the regional autonomy system requires regional government officials could manage finances in their regions effectively and efficiently. The purpose of this study is to analyze the Jambi City Government financial performance during 2010 to 2019 seen from regional financial independence, the degree of decentralization ratio, the effectiveness of PAD ratio, PAD growth ratio, and expending efficiency ratio. This research is a quantitative descriptive study using secondary data, which is sourced from Jambi City Government Budget Realization Report from 2010 to 2019. The results of this study to indicate the financial performance of Jambi City government, seen from regional financial independence ratio, is depressed level, the pattern of instructive relationship, the degree of decentralization ratiois in the low category, the effectiveness ratio are belong to very effective, the average income growth ratio is 11,16 percent and the average expenditure growth is 10,82 percent, and the expending efficiency ratio is classified as efficient.